The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/cells9122678
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aquaporins in the Physiological Functions of Mesenchymal Stem Cells

Abstract: Aquaporins (AQPs) are a family of membrane water channel proteins that control osmotically-driven water transport across cell membranes. Recent studies have focused on the assessment of fluid flux regulation in relation to the biological processes that maintain mesenchymal stem cell (MSC) physiology. In particular, AQPs seem to regulate MSC proliferation through rapid regulation of the cell volume. Furthermore, several reports have shown that AQPs play a crucial role in modulating MSC attachment to the extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 156 publications
0
8
0
3
Order By: Relevance
“…Recently, ophthalmic research has been focused on aquaporins (AQPs), a family of water channel proteins that controls osmotically driven water and fluid transport across cell membranes. The authors underlined the following functional roles of AQPs in the eye function: water balance maintenance to ensure transparency in cornea and lens, aqueous humor production, corneal wound healing and regulation of the tear film osmolarity and retinal homeostasis [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ophthalmic research has been focused on aquaporins (AQPs), a family of water channel proteins that controls osmotically driven water and fluid transport across cell membranes. The authors underlined the following functional roles of AQPs in the eye function: water balance maintenance to ensure transparency in cornea and lens, aqueous humor production, corneal wound healing and regulation of the tear film osmolarity and retinal homeostasis [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As it pertains to changes in cell fluids in response to inflammation, an important role would be played by aquaporins (AQP) [ 85 , 86 ]. AQPs are a group of membrane channel proteins that facilitate the passive transport of water within the cell.…”
Section: Resultsmentioning
confidence: 99%
“…The same forces developed by the movement of fluids, such as FSS and IFP, relative to an LGI, can determine alterations in the function and shape of the tissue itself [ 68 , 75 , 76 , 80 , 81 , 84 ]. At the cellular level, AQP-mediated fluid shifts could play a predominant role in tissue alterations, taking into account that these membrane channels respond to inflammatory phenomena [ 85 , 86 , 88 , 89 , 90 ]. Biological water would react to a series of mechanisms related to inflammation that could be explained by biophysics.…”
Section: Discussion and Hypothesismentioning
confidence: 99%
“…Very recent transcriptomes throughout swine estrous cycle studies revealed that ovarian steroids and cytokines regulate endometrial gene expression during the estrous cycle [43]. Molecular studies have already elucidated the physiological functions of aquaporins and their contribution to the mechanism responsible for balancing water concentration within the uterus [2,6,40,44]. Furthermore, the quality and quantity of the uterine fluid are modified in correlation with fluctuations of estrogen and progesterone during the estrous and menstrual cycle [11,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%